DERMAL FAT GRAFT VERSUS BONE GRAFT FOR MAXILLARY AUGMENTATION IN CLEFT RHINOPLASTY - KHAN, I; AWAN, A; ABBAS , M; AYUB, S; AYUB, AUS (Biological and Clinical Sciences Research Journal, 2024)
Maxillary hypoplasia is common in patients with cleft lip and palate deformities, often leading to aesthetic and functional concerns. Objectives: The study's main objective is to find the dermal fat graft versus bone graft for maxillary augmentation in cleft rhinoplasty. Methods: This retrospective study was conducted at Burns and Plastic Surgery Center Hayatabad Medical Complex Peshawar from December 2021 to December 2022. Data were collected from 58 patients who underwent cleft rhinoplasty. Data were collected from 58 patients according to inclusion and exclusion criteria. All the data related to demographics, history, surgery, and post, and preoperative outcomes were noted for this study. Results: Data were collected from 58 patients from both genders. At the preoperative stage, patients undergoing dermal fat grafting reported a mean VAS score of 2.5 ± 0.3, while those receiving bone grafts had a slightly higher score of 3.0 ± 0.4. However, by 3 months postoperative, both groups experienced substantial increases in satisfaction, with mean VAS scores of 6.2 ± 0.6 for dermal fat grafts and 6.8 ± 0.7 for bone grafts. These improvements continued at 6 and 12 months, with mean VAS scores reaching 7.5 ± 0.8 and 8.0 ± 0.7 for dermal fat grafts, and 8.3 ± 0.9 and 8.7 ± 0.8 for bone grafts, respectively. Conclusion: It is concluded that both dermal fat graft and bone graft are viable options for maxillary augmentation in cleft rhinoplasty. While dermal fat graft may offer superior aesthetic outcomes and reduced donor site morbidity, bone graft provides greater structural support and long-term stability.